Polymorphous Low-Grade Adenocarcinoma of Submandibular Gland - Binesh, Fariba; Akhavan, Ali; Nafis Moghadam, Reza (Reports of Radiotherapy and Oncology, 2015)
Introduction: Polymorphous low-grade adenocarcinoma (PLGA) occurs mostly in minor salivary glands, and there are only a few reports of major salivary gland origin. Case Presentation: We herein report a case of de novo PLGA arising in a submandibular gland in an 88 years-old woman. On examination, a large firm and non-tender mass was palpable in the submandibular region. Conclusions: Neither lymphadenopathy nor enlargement of any other salivary glands was present. CT showed a well-defined mass with irregular enhancement in the submandibular gland.